Case Report: A New Family With Pontocerebellar Hypoplasia 10 From Sudan - Amin, Mutaz; Vignal, Cedric; Hamed, Ahlam A. A.; Mohammed, Inaam N.; Elseed, Maha A.; Abubaker, Rayan; Bakhit, Yousuf; Babai, Arwa; Elbadi, Eman; Eltaraifee, Esraa; Mustafa, Doua; Yahia, Ashraf; et al. (Frontiers in Genetics, 2022)
Pontocerebellar hypoplasia type 10 (PCH10) is a very rare autosomal recessive neurodegenerative disease characterized by intellectual disability, microcephaly, severe developmental delay, pyramidal signs, mild cerebellar atrophy, and white matter changes in the brain, as shown by magnetic resonance imaging (MRI). The disease has been described in only twenty-one patients from ten Turkish families with a founder missense pathogenic variant in the CLP1 gene involved in tRNA processing and maturation. We analyzed three siblings from a consanguineous Sudanese family who presented with intellectual disability, dysmorphic features, developmental delay, regression of milestones, microcephaly, epilepsy, extrapyramidal signs, mild pontine, and cerebellar atrophy. We identified through whole-exome sequencing the same pathogenic variant (c.419G>A; p(Arg140His) reported before in all Turkish families. Our study extends the phenotypes of PCH10 and reports for the first time cases with PCH10 of non-Turkish origin.